Té en domingo - Cooper, Lettice ((Selecciones del Séptimo Círculo ;)
Lettice Cooper escritora inglesa, reside en Londres. Sus obras: We Have Come to the a Country, The New House, National Provincial, Black Bethlehem, A certain Compass, The Double Heart y Late in the Afternoon.